2019
DOI: 10.3126/mjsbh.v18i2.22207
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Metabolic Syndrome in Patients With Type 2 Diabetes Mellitus in a Tertiary Care Hospital

Abstract: Introduction: Diabetes mellitus is associated with various metabolic disorders, which leads to the progression of the disease and its complications. The aim of the study is to find out prevalence of metabolic syndrome and its association with the components and demographic variables. Methods: This cross-sectional study was conducted among diabetes mellitus patients at a Tertiary level teaching hospital over a period of one year (April 2015 to March 2016). The study involved the use of a questionnaire to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
0
1
Order By: Relevance
“…Our study found a high prevalence of dyslipidemia followed by hypertension while Shakya D et al showed high prevalence of central obesity followed by hypertension [13].…”
Section: Discussionsupporting
confidence: 42%
“…Our study found a high prevalence of dyslipidemia followed by hypertension while Shakya D et al showed high prevalence of central obesity followed by hypertension [13].…”
Section: Discussionsupporting
confidence: 42%
“…12 Our study found a high prevalence of dyslipidemia followed by hypertension while Shakya et al showed high prevalence of central obesity followed by hypertension. 13 Our research found prevalence of 76.3% and 61.9% in male and female respectively, showing a higher prevalence in male while the research conducted by Bhattarai et al showed higher prevalence in female with prevalence of male and female of 72% and 91% respectively. 11 Anthropometric indices such as weight, height and waist (cm) were significantly higher in the male population compared to female population in our study are similar to the study done in Gwalior, India.…”
Section: Discussioncontrasting
confidence: 40%